2010
DOI: 10.1099/jmm.0.022103-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographical particularity of the Mycobacterium tuberculosis Beijing family in South Korea based on international comparison with surrounding countries

Abstract: To understand the domestic population structure of Mycobacterium tuberculosis clinical isolates in the Republic of Korea, we genotypically analysed 80 isolates obtained from various geographical origins in the country. Of these, 64 (80.0 %) isolates were identified as Beijing family strains. It is particularly interesting that their phylogenetic classification, based on the ancient/ modern separation and the presence/absence of the genomic region RD181, revealed a majority of the ancient (RD181+) subfamily in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 28 publications
3
34
0
Order By: Relevance
“…The correlations of genotypes based on 45 SNPs were analyzed across the other acceptable genotypic markers for M. tuberculosis. Previously published data and the genotyping results of 183 M. tuberculosis isolates revealed results concordant with spoligotyping and PGG results and were related to the presence or absence of TbD1, RD105, and RD181 and the orientation of IS6110 at the NTF region (24,(32)(33)(34)(35) (Table 3). The investigation of known spoligotype isolates, along with the previously published results, revealed that this SNP set was more informative for subgenotyping the BJ family (SCG2) ( Table 4).…”
Section: Determination Of the Feasibility Of The Modified Digitag2 Assupporting
confidence: 50%
“…The correlations of genotypes based on 45 SNPs were analyzed across the other acceptable genotypic markers for M. tuberculosis. Previously published data and the genotyping results of 183 M. tuberculosis isolates revealed results concordant with spoligotyping and PGG results and were related to the presence or absence of TbD1, RD105, and RD181 and the orientation of IS6110 at the NTF region (24,(32)(33)(34)(35) (Table 3). The investigation of known spoligotype isolates, along with the previously published results, revealed that this SNP set was more informative for subgenotyping the BJ family (SCG2) ( Table 4).…”
Section: Determination Of the Feasibility Of The Modified Digitag2 Assupporting
confidence: 50%
“…Supply et al reported that M. tuberculosis lineages are distinguished by a minimum spanning tree (MST) of 24-MIRU-VNTR profiles of cosmopolitan isolates (Supply et al, 2006). Moreover, previous reports describe that VNTR clustering of detailed sublineages of the Beijing family was observed according to the phylogenetic classification (Kang et al, 2010;Maeda et al, 2010;Merker et al, 2015). These findings indicate that the phylogeny of M. tuberculosis can be estimated properly from VNTR genotypes that were originally improved to trace transmission routes.…”
Section: Introductionmentioning
confidence: 84%
“…These two subfamilies are classifiable further into refined types of sequences (STs) using the patterns of 10 single-nucleotide polymorphisms (SNPs) identified by genomic comparison among referential strains (Filliol et al, 2006;Iwamoto et al, 2008;Nakanishi et al, 2013). Such detailed subdivisions reflect the phylogeographical variation of the Beijing family in countries of eastern Asia (Kang et al, 2010;Wada et al, 2009b). The most outstanding features of the genetic population structure are found in Japan, located at the far eastern edge of Asia.…”
Section: Introductionmentioning
confidence: 97%
“…In other high-BJ-burden countries, such as China, a high prevalence of modern BJ strains has also been reported; however, in other countries, such as Japan and South Korea, more strains from ancestral BJ genotypes (ST3 and ST19 in Japan and ST11 or ST26 in South Korea) have been found. Modern BJ genotypes (ST10 and ST22) are also predominant in Taiwan and Peru (17,18,29). The close historical relationship between China (39) and Japan (17) might be responsible for the BJ sublineages in Thailand.…”
Section: Discussionmentioning
confidence: 99%